دور الأدوات والإجراءات المستخدمة في عملية التوظيف،دراسة حالة لدى عينة من الموظفين المثبتين بمستشفى رزيق البشير –بوسعادة – ولاية المسيلة - مومن, نوارة; بسكر, حدة (جامعة الوادي - University of Eloued, 2018)
تهدف هذه الدراسة إلى التعرف على أهم الأدوات والإجراءات لعملية التوظيف في الجزائر لدى عينة من الموظفين المثبتين بمستشفى رزيق البشير،ولتحقيق أهداف الدراسة تم إستخدام المنهج الوصفي التحليلي واعتماد على استبيان طرق التوظيف وهو يقيس أهم الإجراءات الوظيفية والإدارية ،وقد تم تطبيقه على عينة قوامها15موظفا مثبتا أختيرت بطريقة قصدية،حيث توصلت نتيجة الدراسة بأن المقابلة هي الأداة المستخدمة في عملية التوظيف وأنه يوجد فعلا أدوات وإجراءات مطبقة في الجزائر تبدأ من عملية الإنتقاء وتنتهي إلى عملية التوظيف.This study is to recognize on the most important of tools and procedures for operation recruitment in Algeria to sample from staff of fixers ina hospital Rezzig Bashir,to achieve objectives of the study was used method descriptive analytical analysis and adoption on aquestionnaire of employment methods,it measures the most importantant procedures functional and administrative,it has been applied a sample strength employee fixers is selected in way intentional the study the interview is he tool used in the recruitment process and it actually exists tools and procedures applied in Algeria start from the process selection and ends recruitment process.
Role Tools and Measures Used in The recruitment process,Case study a sample Staff installed of Hospital Rezig Bachir in Bou-Saâda - state of Msila
مقال
Keywords: الأدوات، التوظيف; tools,process.